Bus and tramways strike for equal pay and war bonuses, 1918 (1918)
1918 1918-1939 "Bus and tramways strike for equal pay and war bonuses, 1918" [EP0062], 1918 Between 18 - 23 August 1918, women bus and tram workers went on strike for the same increase [five shillings a week] in the war bonus as men workers. The strike was supported by the London and Provincial Union of Licensed Vehicle Workers. On August 30, the Committee on Production awarded the full backdated increase to the women and extended the increase to munitions workers. These press cuttings also report that the strike was spreading to women working on the Bakerloo line on the London Underground railway.